Oral Metastasis of Metaplastic Breast Carcinoma in a Patient with Neurofibromatosis 1 - Ana Paula Molina Vivas; Luana Eschholz Bomfin; Clovis Antonio Lopes Pinto; Ulisses Ribaldo Nicolau; Fabio Abreu Alves (Case Reports in Oncological Medicine)
Neurofibromatosis type 1 (NF1) has been associated with an increased risk for development of malignancy, especially malignant peripheral nerve sheath tumors. In addition, recently, literature has demonstrated an increased risk of breast cancer in women with NF1. The present paper shows a 53-year-old woman with NF1 who presented with metaplastic breast carcinoma and developed multiple metastases, including mandible. Furthermore, we reviewed the English literature, found 63 cases showing the association between NF1 and breast cancer, and added one more case. The present study demonstrated an important association between NF1 and breast cancer. Until the present time, there has been only one case of metaplastic breast carcinoma associated with NF1. Curiously, in our case the oral metastasis corresponded to sarcomatous component of metaplastic breast carcinoma.